Progress in research and development of preventive vaccines for children in China - Zheng, XuYang; Jin, Ge (Frontiers in Pediatrics, 2024)
The infant and child stage is an important stage for the continuation and development of human society. The initial years of life have a lasting impact on a child's future. Children under the age of 5 have an immature immune system, especially infants and young children under 6 months of age.At this stage, the population has a low immunity to pathogen infections, making them vulnerable to bacteria and viruses. Vaccination can enhance the immunity of infants and children to specific diseases, reduce the transmission rate of infectious diseases, and promote the development of global public health. This article summarizes the current application status of Rotavirus (RV) vaccine, Hand-foot -mouth disease (HFMD) vaccine, and Pneumococcal Conjugate Vaccine (PCV) in China, as well as the research progress of clinical trial vaccine, laying a foundation for subsequent vaccine development.